Development of an Instrument for Measuring the Teachers’ Concerns Based on the Concepts of the Concern-Based stage theory - Nakpat, Jirawan; Wongwanich, Suwimon (Scholar: Human Sciences, 2015)
This research was aimed at developing an instrument for measuring teachers‘ concerns according to the Concern-Based Stage Theory by using content validity analysis and construct validity analysis through confirmatory factor analysis. The analysis results found that the teachers‘ Concern Component Model corresponded to the empirical data. When analyzed with the Structural Equation Model (SEM) analysis program, the analysis results comprised 3 aspects of the principles of teaching concern i.e. self, task and impact on students with another 14 sub-components.